2017
DOI: 10.1515/romneu-2017-0089
|View full text |Cite
|
Sign up to set email alerts
|

Primary sinonasal undifferentiated carcinoma with intracranial extension presenting postoperatively as garcin syndrome: a rare case report and review of literature

Abstract: Sinonasal undifferentiated carcinoma (SNUC) is an aggressive malignancy originating in the mucosa lining the walls of the nasal cavity and paranasal sinuses. It is a rare tumor that usually presents in an advanced stage, is highly invasive, and is traditionally reputed to be refractory to even the most radical therapy with an attendant poor prognosis. This is particularly true when it transgresses the cranial base.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Prasad et al [ 29 ] reported a 43-year-old man with bifrontal headache and nasal obstruction within the last 3 months. He was neurologically intact.…”
Section: Discussionmentioning
confidence: 99%
“…Prasad et al [ 29 ] reported a 43-year-old man with bifrontal headache and nasal obstruction within the last 3 months. He was neurologically intact.…”
Section: Discussionmentioning
confidence: 99%